Bank Concentration and Product Market Competition. (30th January 2021) - Saidi, Farzad; Streitz, Daniel
Abstract: This paper documents a link between bank concentration and markups in nonfinancial sectors. We exploit concentration-increasing bank mergers and variation in banks' market shares across industries and show that higher credit concentration is associated with higher markups and that high-market-share lenders charge lower loan rates. We argue that this is due to the greater incidence of competing firms sharing common lenders that induce less aggressive product market behavior among their borrowers, thereby internalizing potential adverse effects of higher rates. Consistent with our conjecture, the effect is stronger in industries with competition in strategic substitutes where negative product market externalities are greatest.